Identification of central business district (CBD) boundaries by space syntax analysis and the case of Elazığ (Turkey) - Şikoğlu, Emrah; Kaya, H. Serdar; Arslan, Handan (Istanbul Teknik Universitesi, Faculty of Architecture, 2020)
The central business district is a phenomenon used in many sciences, especially in geography. Various techniques have been developed to define the boundaries of this area. While the boundaries of CBD generally depend on the observation and experiences of the researcher conducting the study, individuals working in different fields of science try to determine the boundaries with various simple calculations. This situation may cause researchers to identify different CBDs in the same area. In this research study, the integration calculation provided by the Space Syntax Analysis method was used to determine the specific locations of the Central Business Districts. The city’s global integration analysis (Segment / Integration HH), local integration analysis (Segment / Integration R800) were conducted using the DeptmapX program. As a result of the study process, it was observed that it is possible to determine the location, size and potential expansion of the central business area with the integration analysis of the Space syntax analysis method. Although it was possible to determine CBD boundaries of a city with this method, it is necessary to evaluate the study’s analysis results by comparing them with field studies in order to reach the most accurate result. © 2020, Istanbul Teknik Universitesi, Faculty of Architecture. All rights reserved.
Keywords: Central business area; Central business district; Elazığ city; Space Syntax analysis; Spatial analysis; Urban geography